Kompleksowość procesu prawotwórczego: [The complexity of the legislative process] (Studia Prawnicze / The Legal Studies, 2023)
The recognition of the complexity of phenomena results in the opposition to such methodological approach which analyses respective phenomena as separated from others, whereas there exists causality between one another, or the one-sided one, where only chosen aspects are taken into consideration — and important ones — totally ignored.Being restricted only to the most important factors that account for the complexity of the legislative process, the following ones should be mentioned:1)         the legislative process is determined by a number of social, economic, political, cultural and other phenomena,2)         the legislative process is connected with the process of articulating and uniting the interests of various classes and social strata,3)         the provisions of the law are connected with other provisions within the framework of particular legislative acts, as well as with the whole system of the law,4)         various aspects of the legislative process are interconnected and make up a specific process of passing resolutions,5)         there is a great number of legal subjects that co-operate in the legislative process,6)         various phases of the legislative process are interconnected,7)         legal phenomena occur on numerous planes.It seems to be to the point to treat the legislative process as a decision-making one, in order to expand the conclusions ensuing from the assumptions that the legislative process is of a complex nature. The more so that such approach was seldom of concern to scholars. The law of the socialist country manifests the will of the working people of towns and in the country. Therefore the legislative process must be the follow up of the political decisions, which aim at integrating the interests of various classes and strata of society that make up the working people of towns and in the country, i.e. the subject to the socialist authority. The co-ordination of the future and present interests of the working people is of outstanding significance. The interconnection between the legislative process and the system of social forces, as well as the necessary articulation and correlation of the interests of various classes and social strata also account for the complexity of the legislative system. The legislative resolutions never appear in isolation as they generally form a chain of decisions — it is a sequence in time, connected with particular stages of the legislative process. Thus it is also a logical sequence — a legislative resolution is determined by the preceding, and determines the following one. Therefore legislative acts which regulate a definite sphere of public relations should be examined in a complex way, not only referred to particular domain of the law, but also treated in the context of the whole legal system. The legislative process is also of a complex nature due to several aspects it comprises. Accordingly, in order to ensure that legal acts are optimal, three aspects should be taken into consideration : the axiological, praxiological and social one. This indicates that it is necessary to ensure the participation of political, social and expert factors in the legislative process. Thus a principle of democracy should be combined with expertise. The fact that the legislative process comprises many aspects accounts for a necessary participation of several subjects, i.e. various subjects to socio-political authorities, state organs, representatives of science and professions. Due to the complicated nature of the process and a great number of the participating subjects it is necessary to point out the stages of the legislative process. For neither a motion accounts for the beginning of the process nor does the enactment of the law indicate its end. The analysis of both the complex reflection of reality in the legislative process and complex interrelations among diagnostic, prognostic and socio-technological elements has indicated how complicated the legislative process is in terms of passing resolutions. This is the outcome of the following factors: objective and subjective difficulties to recognize the actual state of affairs, the lack of jurisdical information (as well as the information pertaining to those spheres of public relations which are being regulated), difficulties to assess the real state of affairs, difficulties to define the objective, the fact that even a perfect and relevant diagnosis can be ineffective due to the wrong selection of means and methods of application. This accounts for a growing need to work out a theory of law based on scientific foundations. The comparison between the legislative process and scientific cognition in its philosophical sense allows to point out the properties of the latter and provide the foundations to the theory of legislation : a complex approach to the examined phenomena, ability to generalize facts and isolate regularites which enable scientific forecasts, knowledge treated as a more or less approximate reflection of reality, as the latter permanently evolves, so the cognitive process can never come to an end. With regard to the legislative process it is necessary to apply and observe consistently the postulates that ensue from the theory of scientific cognition. Accordingly, the legislative process should be based on more comprehensive information, that will also be scientifically grounded, on a more thorough outlook into the functioning of the law in force. It is necessary to promote prognostic research in legal studies, as the former has been markedly neglected. Parallel to the process of scientific cognition the legislative one is tantamount to a gradual advancement towards optimal measures. The dynamic development of social reality and its planned progress towards socialism requires that legislative activities are subject to planning. The paper provides the characteristics of the transformations that the legislative process underwent after the VI and VII congress of the Polish United Workers’ Party, and the conclusions ensuing from the hitherto experience relating to the implementation of the government programme of the improvement of the legal system. The complexity of measures applied to this end should be considered as the most significant achievement of the passed period. This, however, cannot cover several weaknesses and imperfections or stay future progress which would find best manifestation in the preparation and enforcement of an act on the enactment of law. It would be of special importance due to its complexity reflected by : thorough approach; embracing both general principles of the enactment of laws and problems of the legislative policy and techniques; the fact that all the stages of the legislative process are embraced, both the stage preliminary to the submitting of a motion and the stage of enforcing the act; taking into consideration all sources of the law in force — this would not only facilitate the improvement of the legislation but also strengthen the supervision over the legislative activies in general.